2015
DOI: 10.1371/journal.pone.0131474
|View full text |Cite
|
Sign up to set email alerts
|

High Incubation Temperature and Threonine Dietary Level Improve Ileum Response Against Post-Hatch Salmonella Enteritidis Inoculation in Broiler Chicks

Abstract: This study assessed the effect of both embryonic thermal manipulation and dietary threonine level on the response of broilers inoculated with Salmonella Enteritidis, considering bacterial counts in the cecal contents, intestinal morphology, mucin and heat shock protein 70 gene expression, body weight and weight gain. Thermal manipulation was used from 11 days of incubation until hatch, defining three treatments: standard (37.7°C), continuous high temperature (38.7°C) and continuous low temperature (36.7°C). Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Dietary supplementation with both Thr and mannan oligosaccharide (MOS) [5] or only Thr [24] has been reported to decrease the number of Salmonella -positive animals and bacterial counts in the cecal contents, similar to the present finding with in ovo Thr supplementation. Some factors may have contributed to decreased Salmonella cecal counts in the Thr-administered group at 168-hour postinoculation (9 days of age).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Dietary supplementation with both Thr and mannan oligosaccharide (MOS) [5] or only Thr [24] has been reported to decrease the number of Salmonella -positive animals and bacterial counts in the cecal contents, similar to the present finding with in ovo Thr supplementation. Some factors may have contributed to decreased Salmonella cecal counts in the Thr-administered group at 168-hour postinoculation (9 days of age).…”
Section: Discussionsupporting
confidence: 83%
“…These results might be associated with preserved intestinal mucosal integrity since the T-SE animals presented similar morphometry to unchallenged animals (T-SHAM and NT-SHAM), while chicks from nonsupplemented groups presented compromised mucosal integrity at all times evaluated (24, 96, and 168 hpi). Improved intestinal integrity was also observed in Salmonella -challenged chicks fed Thr in the diet [24]. These results indicate that in ovo Thr supplementation reduced the burden of Salmonella toxins in the gut of broiler chicks.…”
Section: Discussionmentioning
confidence: 74%
“…Chickens challenged with E. coli in the present study showed an upregulated expression of MUC2, which is in line with previous reports 43,44 . It was shown that the expression of MUC2 increased in the infectious challenge to secrete more mucin from goblet cells into the intestinal lumen to support the protective layer between the invading bacteria and the epithelial cells 45 . Adding AMP to the diet downregulated the expression of MUC2 in the jejunum of challenged chickens, which may be attributed to the significant inhibitory effect of cLF36 on E. coli colonization in the intestine (as described above), which is in agreement with previous observation 46 .…”
Section: Discussionmentioning
confidence: 99%
“…At day 42 posthatch, no differences in NCD antibody titers or swelling reaction in the wattle to Phytohemagglutinin-P injection were found. Increasing incubator temperature by 1°C from day 10 of incubation onward compared with a constant incubator temperature of 37.8°C was found to increase mucin expression and reduce colonization of Salmonella Enteritidis in the cecal content of 10-day-old broilers when inoculated with Salmonella Enteritidis at 2 d posthatch ( De Barros Moreira Filho et al., 2015 ). Somewhat contradictory, the same thermal manipulation treatment by Oznurlu et al.…”
Section: Introductionmentioning
confidence: 99%